Identification of Key Tissue-Specific, Biological Processes by Integrating Enhancer Information in Maize Gene Regulatory Networks - Fagny, Maud; Kuijjer, Marieke Lydia; Stam, Maike; Joets, Johann; Turc, Olivier; Rozière, Julien; Pateyron, Stéphanie; Venon, Anthony; Vitte, Clémentine (Frontiers in Genetics, 2021)
Enhancers are key players in the spatio-temporal coordination of gene expression during numerous crucial processes, including tissue differentiation across development. Characterizing the transcription factors (TFs) and genes they connect, and the molecular functions underpinned is important to better characterize developmental processes. In plants, the recent molecular characterization of enhancers revealed their capacity to activate the expression of several target genes. Nevertheless, identifying these target genes at a genome-wide level is challenging, particularly for large-genome species, where enhancers and target genes can be hundreds of kilobases away. Therefore, the contribution of enhancers to plant regulatory networks remains poorly understood. Here, we investigate the enhancer-driven regulatory network of two maize tissues at different stages: leaves at seedling stage (V2-IST) and husks (bracts) at ﬂowering. Using systems biology, we integrate genomic, epigenomic and transcriptomic data to model the regulatory relationships between TFs and their potential target genes and identify regulatory modules speciﬁc to husk and V2-IST. We show that leaves at the V2-IST stage are characterized by the response to hormones and macromolecules biogenesis and assembly, which are regulated by the BBR/BPC and AP2/ERF TF families, respectively. In contrast, husks are characterized by cell wall modiﬁcation and response to abiotic stresses, which are respectively orchestrated by the C2C2/DOF and AP2/EREB families. Analysis of the corresponding enhancer sequences reveals that two different transposable element families (TIR transposon Mutator and MITE Pif/Harbinger) have shaped part of the regulatory network in each tissue, and that MITEs have provided new TF binding sites involved in husk tissue-speciﬁcity.